Yoga Pranayama Reduce Anxiety Facing Labor In Pregnant Women Trimester III at PMB in the work area of the Abiansemal I Health Center - Widiastini, Luh Putu; Manik Karuniadi, I Gusti Agung (Jurnal Kesehatan Pasak Bumi Kalimantan, 2022)
Women during pregnancy will experience physiological changes and psychological changes. Changes that occur can cause feelings of fear, anxiety, so that it affects pregnancy and childbirth. The purpose of this study was to determine the effect of pranayama yoga on the anxiety of pregnant women in dealing with childbirth at PMB in the work area of the Abiansemal I Health Center. This study used a quantitative research method with a Quasy experimental type of research. The design used in this study is a nonequivalent control group design, the sample is carried out by non-probability sampling, namely total sampling. The sample in this study was 70 pregnant women who would be divided into two groups, namely 35 for the treatment group who would be given yoga pranayama and 35 people for the control group who would be given leaflets. The data were analyzed using analysis using the Mann-Whitney test with a confidence level of p≤0.05. The results show significance for the experimental group given the yoga pranayama technique, namely p value = 0.000, so it can be concluded that there is a significant effect of pranayama yoga technique on anxiety facing labor in third trimester pregnant women